Segmental cues to intonation of statements and polar questions in whispered, semi-whispered and normal speech modes. (July 2017) - Żygis, Marzena; Pape, Daniel; Koenig, Laura L.; Jaskuła, Marek; Jesus, Luis M.T.
Highlights: Whispered speech encodes intonation despite F0 absence. Not only vowels but also consonants vary with intended intonation. Voiceless obstruents reflect intonational differences in different speech modes. Some unique intonational differences in whispered consonants may compensate for the missing F0. Abstract: This paper examines how acoustic characteristics of vowels and consonants reflect intonational differences between polar questions and statements in Polish whispered, semi-whispered and normal speech modes, with particular focus on the spectral characteristics of voiceless consonants as a function of intonation, and across speech modes. The results reveal significant differences in spectral properties of both utterance-final vowels and consonants across statements and polar questions. Questions have higher vowel intensities and show differences in formant frequencies that vary with speech mode. Regarding the consonants, both fricatives and affricates are produced with higher intensity, spectral peaks at higher frequencies, and higher Centre of Gravity and Spectral Standard Deviation values in questions than in statements. Conversely, skewness and kurtosis are lower in questions than in statements. Some spectral features of sibilants, including spectral slopes, show greater question-statement differences in the whispered speech mode than in other speech modes. The finding that some cues are more pronounced in whispered speech suggests that they may compensate for the absence of fundamental frequency in this mode. Most generally, the study shows that speakers produce intended intonation patterns by varying the type and magnitude of cues depending on speech mode.